PD-L1 and PD-1 and characterization of tumor-infiltrating lymphocytes in high grade sarcomas of soft tissue – prognostic implications and rationale for immunotherapy. (4th March 2018) - Boxberg, Melanie; Steiger, Katja; Lenze, Ulrich; Rechl, Hans; von Eisenhart-Rothe, Rüdiger; Wörtler, Klaus; Weichert, Wilko; Langer, Rupert; Specht, Katja
ABSTRACT: Therapies targeting programmed death 1-(PD-1) or its ligand (PD-L1), promoting antitumor T-cell activity have been successfully introduced into clinical practice. Clinical response correlates with PD-L1 expression by tumor cells or immune cells within the tumor microenvironment. The PD-L1/PD-1 axis and tumor microenvironment has been rarely studied in high-grade sarcomas of soft tissue (hSTS), a group of rare, genetically heterogenous and clinically aggressive tumors. We examined PD-L1 protein and CD274/PD-L1 gene copy number variations in 128 primary resected, therapy-naive hSTS using immunohistochemistry and fluorescence-in-situ hybridization. Frequency of tumoral PD-L1 expression varied widely in different disease subentities, with highest rates of positivity (40%) seen in undifferentiated pleomorphic sarcomas (UPS) and rare positivity detected in synovial sarcomas (6%). Amplification of the CD274/PD-L1 gene occurred in 14% of UPS and was rare in other subtypes. PD-L1 protein expression was significantly more frequent in CD274/PD-L1 amplified cases (p = 0.015). The subgroup of UPS was further characterized regarding the interaction between PD-L1 and the immunologic tumor microenvironment. High density of CD3+ and CD8+ tumor infiltrating lymphocytes (TILs) was significantly correlated with the presence of PD-L1 expression and seen more frequently in tumors with lower TNM stage (p = 0.024). Both, PD-L1 expression and high density lymphocytic infiltration were independent prognostic factors for a favorable overall (p = 0.001, HR 6.105 (2.041–8.258)), disease-specific (p = 0.003, HR 10.536 (2.186–50.774)) and disease-free survival (p = 0.020, HR 3.317 (1.209–9.106); values for CD8) in this particular subgroup of hSTS, whereas PD-L1 expression in TILs or CD274/PD-L1 gene amplification were not associated with outcome. These findings represent novel insights into the immune landscape of soft tissue sarcomas, in particular UPS and strengthen the rationale for immunotherapy, including targeting the PD-1/PD-L1 axis in these tumors.